PENGARUH FAKTOR SUMBER DAYA MANUSIA, BIAYA, BAHAN, DAN PERALATAN TERHADAP PENYELESAIAN PROYEK PEMBANGUNAN GEDUNG ASRAMA TERPADU MAN 2 FLORES TIMUR - Ropi, Sarina S.; Meo, Yohanes; Gado, Alfridus (TEKNOSIAR, 2021)
According to the contract, the implementation of the work on the construction of the East Flores MAN 2 integrated dormitory building project ending on December 31 2020 has reached 100%, but only 3.68% of the project has experienced delays. This study aims to determine the effect of human resource factors, costs, materials and equipment on the completion of the East Flores MAN 2 integrated dormitory building project. With a quantitative descriptive method. The data for this study were sourced from questionnaires distributed to 25 respondents who were stratified by population stratification into project owners, contractors, consultants, foremen, builders, and laborers. The results of the analysis obtained sig. Human resources of 0.028 <0.05 and t count -23.067 > t table 12.71. sig. value Cost of 0.041 <0.05 and t count 15.635 > t table 12.71. sig. value Material of 0.006 <0.05 and t count 98.758 > t table 12.71. sig. value Equipment of 0.017 <0.05 and t count -37.437 > t table 12.71. The conclusion is that there is an influence of human resource factors, costs, materials, and equipment on the completion of the East Flores MAN 2 integrated dormitory building project, and material factors are the most influential.